2006
DOI: 10.5935/0104-7795.20060002
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Brazilian version of the McGill pain questionnaire in elderly patients with chronic pain

Abstract: A dor crônica é uma experiência multidimensional que envolve aspectos sensório-perceptual, afetivo-motivacional e cognitivo-avaliativo que se interagem e contribuem para a resposta dolorosa final. As alterações características do processo do envelhecimento em cada um desses aspectos podem interferir na experiência da dor, dificultando a sua avaliação adequada. O uso de uma escala multidimensional como o Questionário de dor McGill (MPQ) possibilita uma avaliação mais adequada desse sintoma. Os objetivos desse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
2
Order By: Relevance
“…A study aimed to evaluate the sensitive, affective, temporal and miscellaneous qualities of pain in elderly people with chronic pain, provide information about the different perceptions of the various factors that are part of the pain symptom, in relation to people with different diseases, since the perception of this symptom is related to sensitive, affective and motivational aspects, and not only to the intensity 16 . Another study shows predominance of chronic pain in elderly people, highlighting the prejudices to the quality of life due to physical and affective dimension of pain, such as inactivity and social isolation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A study aimed to evaluate the sensitive, affective, temporal and miscellaneous qualities of pain in elderly people with chronic pain, provide information about the different perceptions of the various factors that are part of the pain symptom, in relation to people with different diseases, since the perception of this symptom is related to sensitive, affective and motivational aspects, and not only to the intensity 16 . Another study shows predominance of chronic pain in elderly people, highlighting the prejudices to the quality of life due to physical and affective dimension of pain, such as inactivity and social isolation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A categoria "afetiva" é composta por palavras relacionadas ao estado emocional do indivíduo, podendo traduzir percepção de cansaço, sentimento de medo e punição e reações autonômicas (Santos et al, 2006). Em contraponto, as "sensoriais" se remetem às percepções e sensações do próprio corpo, adquirindo um caráter mais concreto e mais facilmente descrito pelas crianças.…”
Section: Resultsunclassified
“…Existem instrumentos para adultos, como o Questionário de dor McGill, que, dentre outros aspectos, possibilita a avaliação da experiência dolorosa prevendo um espaço para a queixa espontânea da dor, por meio de um conjunto de palavras que descrevem diversas qualidades das experiências dolorosas em geral e que são escolhidas pelos pacientes para caracterizar as suas dores em particular (Santos, Pereira, Resende, Magno, & Aguiar, 2006). Tratam-se de descritores de dor caracterizados em subcategorias: "afetivo", "sensitivo" e "avaliativo".…”
Section: Segundo a International Association For The Study Ofunclassified
“…The study by Santos et al 27 showed that the older population may overestimate the pain sensation, exceeding the description of pain intensity, especially when it involves some decline in cognitive function, or when measured by a one-dimensional scale, which justifies the use of Br-MPQ. Older people mistakenly believe that this painful symptom is a component of the aging process [27][28] . In this study, we can observe that individuals with high performance in tests of upper and lower limb strength show high levels of pain intensity.…”
Section: Discussionmentioning
confidence: 99%